Linkage of Chronic Disease Data from Provincial Sources for Strategic Decision Support and Population Health Surveillance in British Columbia (BC). (2018) - Rasali, Drona; Djurdjev, Ognjenka; Li, Crystal; Ord, Edward; Laberge, Carol; Woods, Ryan; John, Spinelli; Ding, Lilian; Ye, Xibiao; Smolina, Kate; Almeida, Alberto
No abstract available